Exploring perceived barriers and attitudes in young adults towards antidepressant pharmacotherapy, including the implementation of pharmacogenetic testing to optimize prescription practices - Roberts, Bradley; Cooper, Zahra; Landery, Georgia; Stanley, Susanne; Majda, Bernadette T.; Collins, Khan R. L.; Akkari, P. Anthony; Hood, Sean D.; Rodger, Jennifer (Frontiers in Pharmacology, 2025)
IntroductionThe field of pharmacogenetics (PGx) is experiencing significant growth, with increasing evidence to support its application in psychiatric care, suggesting its potential to personalize treatment plans, optimize medication efficacy, and reduce adverse drug reactions. However, the perceived utility and practicability of PGx for psychiatric treatment in youth remains underexplored. This study investigated perceived barriers and attitudes in Australian young adults towards the implementation of PGx testing to guide antidepressant treatment in primary care.MethodsSemi-structured focus groups and interviews were conducted with 17 participants aged between 18 and 24 years. These sessions were recorded and transcribed before thematic analysis was used to identify collective themes.ResultsThree key themes were identified, including attitudes towards the medication prescription process, concerns and attitudes towards PGx testing, and perceived barriers to its clinical implementation. Although PGx testing was positively perceived by most participants, all participants shared concerns about PGx testing. Participants voiced concerns about the financial impact of PGx testing, the potential for treatment delays, and the accuracy of PGx testing in guiding antidepressant treatment. Additionally, participants noted that the low awareness and willingness of general practitioners to incorporate PGx testing into routine practice could hinder successful clinical implementation.DiscussionPrior to the implementation of PGx testing into Australian primary practices, it is essential to acknowledge patient perspectives and ensure that clinical practices remain patient-focused. This study highlights important considerations for integrating PGx testing into antidepressant pharmacotherapy and emphasizes the need for future research to address and mitigate the perceived barriers of young adults.